MITOS AUL DI ERA DIGITAL: STRATEGI KOMUNIKASI LINGKUNGAN MELALUI ADAPTASI BUKU MANUSIA DAN GUNUNG DAN FILM DOKUMENTER AKSATRIYA - Nurman Fauzi, Yudi; Yulianeta; Permadi, Tedi; Didin Wahyudin, Pepep (PANGGUNG, 2025)
This study examines the transformation of the Aul myth—a part of the oral tradition of the Sundanese people—into two modern media: the book Manusia dan Gunung and the documentary film Aksatriya. The main objective is to explore how these media represent ecological values through transmedia strategies and culturally rooted narratives. This qualitative-descriptive research employs narrative analysis, close reading for the book, close viewing for the film, and documentation of oral traditions. The findings indicate that the book offers a reflective and symbolic narrative that fosters ecological awareness through literary depth. In contrast, the documentary film conveys the collective voice of the community by presenting testimonies, natural landscapes, and audiovisual aesthetics to reconstruct the meaning of Aul as a guardian of nature. Both mediums not only preserve local cultural heritage but also reinterpret myth to meet the challenges of contemporary environmental crises. The study concludes that transmediabased adaptation strategies can serve as inclusive and effective conservation narratives. These findings contribute to the development of culturally embedded ecological education and policies grounded in local wisdom.